ASSESSMENT OF POSTOPERATIVE PAIN AFTER SINGLE-VISIT VERSUS MULTIPLE-VISIT ROOT CANAL TREATMENT USING DIFFERENT IRRIGANTS - Dr Omkar Eswara Babu Danda; Dr Jitendra Sharan; Dr Tarun Kumar Singh; Dr.G.V.Mohandas; Dr. Afroz kalmee syed (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Postoperative pain following root canal treatment remains a common patient concern and may be influenced by the number of visits and irrigant used during chemomechanical preparation.Aim:To evaluate and compare postoperative pain after single-visit and multiple-visit root canal treatments using two different irrigants: 5.25 % sodium hypochlorite (NaOCl) and 2 % chlorhexidine (CHX).Materials and Methods:A randomized controlled clinical trial was conducted on 300 patients requiring primary endodontic therapy. Participants were divided into four groups (n = 75 each): single-visit + NaOCl, single-visit + CHX, multiple-visit + NaOCl, and multiple-visit + CHX. Postoperative pain was assessed using a 100 mm visual analogue scale (VAS) at 6, 12, 24, 48, and 72 hours. Analgesic use and flare-ups were recorded. Statistical analysis included ANOVA, chi-square, and two-way ANOVA tests with p < 0.05 considered significant.Results:Single-visit groups demonstrated significantly higher pain scores at 6 h and 12 h (p < 0.05), which diminished by 24 h. No significant differences were observed between irrigants. Analgesic use and flare-ups were minimal and comparable among groups.Conclusion:Both single- and multiple-visit root canal treatments are safe and effective. Multiple-visit protocols may reduce early postoperative pain, while irrigant type exerts minimal influence on pain outcomes.